Adaptive radiotherapy for breast cancer. (March 2023) - De-Colle, C.; Kirby, A.; Russell, N.; Shaitelman, S.F.; Currey, A.; Donovan, E.; Hahn, E.; Han, K.; Anandadas, C.N.; Mahmood, F.; Lorenzen, E.L.; van den Bongard, D.; et al.
Highlights: Adaptive radiotherapy offers potential clinical benefits for breast cancer patients. Advantages of MR-guided adaptive radiotherapy are expected in the neoadjuvant setting. Autonomous aritifical intellingence-driven technologies might further enable adaptive radiotherapy. Abstract: Research in the field of local and locoregional breast cancer radiotherapy aims to maintain excellent oncological outcomes while reducing treatment-related toxicity. Adaptive radiotherapy (ART) considers variations in target and organs at risk (OARs) anatomy occurring during the treatment course and integrates these in re-optimized treatment plans. Exploiting ART routinely in clinic may result in smaller target volumes and better OAR sparing, which may lead to reduction of acute as well as late toxicities. In this review MR-guided and CT-guided ART for breast cancer patients according to different clinical scenarios (neoadjuvant and adjuvant partial breast irradiation, whole breast, chest wall and regional nodal irradiation) are reviewed and their advantages as well as challenging aspects discussed.